A study on leaching characteristic of coal ash from landfills - Jesper Hansen, Lawrence Jema-Ee (Universiti Malaysia Sarawak (UNIMAS), 2009)
This study detennined the content of minor trace elements in coal ash collected from a coal-fired thermal power plant using local coal from Sarawak, Malaysia. This is crucial for the. potential impact on the geoenvironment from its disposal and utilization. A fabricated model is designed to study the leaching characteristic of coal ash. The leachability of the constituents such as minor trace elements in the coal fly ash was studied. The parameters namely pH, cumulative release regarding the minor trace elements to duration was presented. The results showed that the pH solutions increased during the test. It might have resulted from the large buffering capacity of the coal ashes. Six elements namely Fe, Cu, Ni, Pb, Cr and Zn were detected in the all leachant solutions samples using the Atomic Absorption Spectrometer (AAS) test. The trace elements concentrations presents in coal ashes were compared with the concentration of minor elements in the Drinking Water Standard Quality by The Ministry of Health of Malaysia. The minor elements were found to be in concentrations that, if applied or inadvertently released into the environmental media, present .., a potential hazard and further necessary research in this regard is indicated.